Characteristics Of The Informal Sector In Denpasar City - Sang Ayu Kompyang Dian PRATIWI; I Ketut DARMA; Anak Agung Sri PURNAMI (Indonesia Strategic Sustainability, 2022)
This research aim to determine the characteristics of the informal sector in the city Denpasar. The sample of this study was 50 respondents who were taken based on non probability sampling and data collection instruments use are questionnaire. The result of this study indicates that the characteristics of informal sector workers when viewed from the social side which is dominated by workers with education last high school (56%), meried status (72%), type of main job (56%), morning working hours (07.00-finished) (64%), daily sales intensity (80%), with fixed place of sale (56%), the average length of sale is less than 5 years (50%), with their own workers (68%). Characteristics when viewed from the demographic side which is dominated by women (58%), with an age range of 27 to more than 40 years (28%), from Karangasem regency (34%), where they live contracting/leasing (58% ), the type of merchandise sold is in the from of goods mixed (34%), with holiday intensity never having a day off (70%). Characteristics of the informal sector when viewed from the economic side, namely strating with initial capital an average or more than Rp. 400,000 (40%), and average monthly income an average of more than Rp. 1,100,000. from Karangasem regency (34%), where they live contracting/leasing (58%), the type of merchandise sold is in the from of goods mixed (34%), with holiday intensity never having a day off (70%).